SPIRITUAL EDUCATION THROUGH THE INTERNET - Samatov Khurshid Olmasovich,; Otaboyev Ahror is the son of Shuhrat, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article analyzes the impact of information and communication technologies on the spiritual education of youth during the process of globalization. It explores the issues of forming "spiritual immunity" against various information attacks on the Internet and the negative consequences of "mass culture". Furthermore, the article provides practical recommendations for preserving national values in the virtual world and enhancing digital culture (netiquette).